2021
DOI: 10.1155/2021/4529009
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemic Periodic Paralysis Precipitated by Thyrotoxicosis and Renal Tubular Acidosis

Abstract: Background. Hypokalemic periodic paralysis is a rare neuromuscular disorder characterized by transient episodes of flaccid paralysis due to a defect in muscle ion channels. Most cases are hereditary, but it can be acquired. We present a case of acquired hypokalemic periodic paralysis associated with hyperthyroidism and renal tubular acidosis. Clinical Case. A 38-year-old female with a history of Graves’ disease presented to the emergency department with generalized weakness and associated nausea, vomiting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Mice deficient in carbonic anhydrase 2 (Car2−/− mice) have metabolic acidosis, impaired urine acidification, and are deficient in normal intercalated cells ( 71 ). The present study showed that the abundance of Ca1 and Ca2 in thyrotoxicosis mice were both downregulated, which might be the reason for hyperthyroidism associated renal tubular acidosis ( 72 ). A study showed that the expression of the Ca2 gene in zebrafish decreased with age, and Ca2 can be used as a biomarker of aging ( 73 ).…”
Section: Discussionmentioning
confidence: 67%
“…Mice deficient in carbonic anhydrase 2 (Car2−/− mice) have metabolic acidosis, impaired urine acidification, and are deficient in normal intercalated cells ( 71 ). The present study showed that the abundance of Ca1 and Ca2 in thyrotoxicosis mice were both downregulated, which might be the reason for hyperthyroidism associated renal tubular acidosis ( 72 ). A study showed that the expression of the Ca2 gene in zebrafish decreased with age, and Ca2 can be used as a biomarker of aging ( 73 ).…”
Section: Discussionmentioning
confidence: 67%
“…4 In the absence of a family history of paralysis, renal tubular acidosis should also be considered. 5 Symptoms of hyperthyroidism may not always be evident in patients, or muscle paralysis could be the first manifestation of thyrotoxicosis. THPP can be complicated with ventricular fibrillation or hypercapnic respiratory failure if not diagnosed and treated promptly.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional case reports with this association were published in 2020, and another study published recently showed a prevalence of 14.81% of DRTA (16 patients) in a cohort of 108 patients with SLE [ 6 , 7 , 8 ]. Generally, the majority of cases with complete DRTA published in literature are diagnosed due to severe symptoms associated with hypokalemia, such as quadriparesis or even respiratory arrest, and therefore, the real prevalence of DRTA associated with autoimmune diseases is difficult to estimate [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, urinary acidification tests are essential in diagnosing those patients who did not develop any symptoms and would otherwise escape undiagnosed.…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Aiming for a better understanding of the disease, we performed a search of the PubMed database using MeSH descriptors (Acidosis, Renal Tubular; Lupus Erythematosus, Systemic; Sjogren’s Syndrome, Systemic Vasculitis, Rheumatoid Vasculitis, Arthritis, Rheumatoid, Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis, Churg-Strauss Syndrome, IgA Vasculitis, Spondylitis, Ankylosing, Cryoglobulins, Hepatitis, Autoimmune, Liver Cirrhosis, Biliary), and we identified 37 individual case reports published since December 2016 with the association of distal renal tubular acidosis and the following autoimmune disorders: SLE, Sjögren’s syndrome, autoimmune hepatitis, primary biliary cirrhosis and rheumatoid arthritis (see Table 1 ) [ 6 , 10 , 11 , 13 , 15 , 16 , 17 , 18 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. We also identified a case of hereditary autoimmune polyendocrine syndrome (DRTA, hypoparathyroidism, Addison disease), published in a series of cases, which was not included in our analysis, due to the lack of individual data availability [ 39 ].…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation